4n-3=4n-3

Simple and best practice solution for 4n-3=4n-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-3=4n-3 equation:


Simplifying
4n + -3 = 4n + -3

Reorder the terms:
-3 + 4n = 4n + -3

Reorder the terms:
-3 + 4n = -3 + 4n

Add '3' to each side of the equation.
-3 + 3 + 4n = -3 + 3 + 4n

Combine like terms: -3 + 3 = 0
0 + 4n = -3 + 3 + 4n
4n = -3 + 3 + 4n

Combine like terms: -3 + 3 = 0
4n = 0 + 4n
4n = 4n

Add '-4n' to each side of the equation.
4n + -4n = 4n + -4n

Combine like terms: 4n + -4n = 0
0 = 4n + -4n

Combine like terms: 4n + -4n = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4y^2+36y+72=0 | | 5/4(a-8=2/3 | | 3x[x-3]=6 | | 600=50+10c | | 7y-3y=18 | | x-0.24x=519.21 | | 2x-9+7x+13+41=180 | | y=-2(x+3)(x-4) | | x-.24x=519.21 | | 1.5y=3y | | x^3*y^3=216 | | ln(x+1)=ln(1.3) | | 5x+5-10(x+1)= | | 7-8p/2=28 | | 2x+8=4x-6 | | -9=6.3 | | 7-8p/2 | | 6x-5=2y+7 | | x*(x*y)*(x*y^2)=216 | | 16+2x=54 | | f(x)=1/5(15x) | | 9x=10+5x | | x*(x*r)*(x)*(y^2)=216 | | (x+11)+x=21 | | 0.5x^2+2x+cos(x)=0 | | 23=8+5x | | 4x+14=7x+2 | | 36x-8+2x=9 | | x+9=5x | | X-(-47)=76 | | -26-4n=-2+2(-4n+4) | | 2x+1=199 |

Equations solver categories